Outcome of patients with tetralogy of Fallot repair over 50 years of age. (25th November 2020) - Antal, A; Szegedi, M; Takacs, E; Szabo, B; Solymosi, B; Vincze, V; Ablonczy, L; Kornyei, L; Temesvari, A; Andreka, P; Balint, H
Abstract: Purpose: To report the outcomes of patients with repaired tetralogy of Fallot (TOF) above 50 years of age. Methods: We reviewed records of TOF patients who were followed in our institution since 2000. Demographic data, surgical reports and long-term outcomes were analyzed retrospectively. Results: Thirty-five of 297 (12%) patients who underwent TOF repair were above 50 years of age (25 men [60%]) at the last follow-up. Eighteen patients (48%) had prior palliative surgery. The mean age at the first repair was 18±13 years (5 patients after 40 years of age). Reoperation with pulmonary valve replacement was performed in 10 (28%) patients, and a second redo surgery in 6 (17%) patients. During a mean 17± 2 years follow-up 7 (8.5%) patients died (n=6 end-stage heart failure, n=1 infective endocarditis). At the last follow-up 21/35 patients (60%) were treated with tachyarrhythmia, 19/35 (54%) with chronic heart failure and 17/35 (48%) with comorbidities (hypertension, coronary artery disease/peripherial artery disease, diabetes mellitus, renal failure). Using multivariate analysis the only predictor of death was heart failure (OR: 6.8). Furthermore atrial tachycardia (OR: 8.8) and at least grade II tricuspid regurgitation (OR: 5.0) were identified as predictors of heart failure. Conclusion: This historical cohort of TOF patients with late repair has a high morbidity rate later in life. Approximately half of the patients require treatment for chronic heart failure, arrhythmias and cardiovascular related comorbidities. Atrial tachycardia and tricuspid regurgitation are strong predictors for heart failure. In this population the strongest predictor for death is heart failure. Funding Acknowledgement: Type of funding source: None